Hybrid excited permanent magnet machines for electric and hybrid electric vehicles - Zhu, Z. Q.; Cai, S. (CES Transactions on Electrical Machines and Systems, 2019)
This paper reviews various hybrid excited (HE) machines from the perspective of location of PM and DC excitation, series/parallel connection of PM and DC excited magnetic fields, and 2D/3D magnetic fields, respectively. The advantages as well as drawbacks of each category are analyzed. Since an additional control degree, i.e. DC excitation, is introduced in the HE machine, the flux weakening control strategies are more complex. The flux weakening performance as well as efficiency are compared with different control strategies. Then, the potential to mitigate the risk of uncontrolled overvoltage fault at high speed operation is highlighted by controlling the field excitation. Since additional DC coils are usually required for HE machines compared with pure PM excitation, the spatial confliction inevitably results in electromagnetic performance reduction. Finally, the technique to integrate the field and armature windings with open-winding drive circuit is introduced, and novel HE machines without a DC coil are summarized.